Patients perceptions towards insulin therapy at Hospital Raja Permaisuri Bainun - Kasim, Nabilah; Padali, Noratiqah (2011)
Diabetes Mellitus is a group of metabolic diseases in which a person has high blood sugar, either because the body does not produce enough insulin, or because cells do not respond to the insulin that is produced [1], This research is to investigate the adherence of insulin therapy among diabetic patients at Hospital Raja Permaisuri Bainun. Our objectives are to identify on the percentage of patients adherence towards insulin therapy, to investigate the percentage of patients who are adherent to therapy has well controlled of blood glucose level or not and to identify patients’ perception about insulin therapy such as fear on insulin injection, interference with daily routine, help control blood glucose level and insulin convenience to carry out. 30 insulin-dependent patients out of 275 of population of diabetic patients’ were surveyed on using insulin injection. Our inclusion criteria include patients’ with type 1 and type 2 diabetes who are using insulin, duration of how long patients using insulin injection, aged 15-75 years old, patients in outpatient pharmacy who have just seen doctor and have laboratory blood glucose result with them. The duration of our survey is 2 months from December 2011 until January 2011 at 2-3pm. Our exclusion criteria are diabetic patients who did not have their laboratory blood glucose result and using oral diabetes medication only. They were surveyed using our questionnaire based on Modified Morisky Medication Adherence Scale. In order to make the questionnaires efficient, we did a pilot study to 4 respondents to ensure of patients’ understanding. Our results determined that 56.67% of the diabetic patients are obtaining average adherence score towards insulin therapy. Meanwhile 20% of the diabetic patients get adherence score and 23.33% get non adherence score. Adherence is the very important aspects in diabetes control. Lack of adherence can lead to many diabetes-related complications. The goal of diabetes management is to keep blood glucose levels as close to a normal range as safely as possible, while avoiding blood glucose levels that are too high (hyperglycemia) or too low (hypoglycemia). We can conclude that most of the patients average adherence score are adherent towards insulin therapy. Adherence to insulin therapy can lead to better outcome of glycaemic control. Patients’ perceptions on insulin therapy that we have discussed are played an important part of adherence towards insulin therapy.